Parametric study on fatique failure using crack initiation method - Mohd Fadzrul Hisyam, Badarudin (2012)
This thesis presents the parametric study on fatigue failure using crack initiation method analysis. In order to investigate the fatigue failure of AISI/SAE 1045 steel by varying the microstrain parameters under different loading cases and predict the crack initiation life, compact tension specimen model is used for this project. The finite element linear static analysis is done by using MSC Patran 2010 and MSC Nastran 2007 to determine the result of the stress distribution on the model. The fatigue analysis is conducted by using ANSYS 13.0 nCode Design Life to determine the microstrain value that initiates the dynamic and static failure under three loading cases; compression-compression, compression-tension and tension-tension. The obtained microstrain values are then used to obtain the fatigue damage, D which is then used to predict the crack initiation life of the material. Using Palmgren-Milner rule, the value of D will obtain the crack initiation life cycle of the material, Nf. Based on the result, it has found that the most critical loading case for the fatigue and static failure are the tension-tension. The crack initiation life of the material is at high cycle fatigue, and able to stand about 5 × 106 cycles without failure for every loading case. Meanwhile the static failure analysis has found that there is no crack initiation life, as it has failed at very low cycle in every loading case.